Disposable Component Selection in Extracorporeal Life Support: A Cost Analysis. Issue 9 (11th December 2020) - Stokes, John W.; Gannon, Whitney D.; Tipograf, Yuliya; Ukita, Rei; Warhoover, Matthew; Rice, Todd W.; Shah, Ashish S.; Bacchetta, Matthew
Abstract : Supplemental Digital Content is available in the text. Abstract : Extracorporeal life support (ECLS) is a resource-intensive technology. Disposable components are modifiable through device selection. Cost analysis tools are needed to inform cost-conscious device selection. We generated a disposable cost analysis to forecast estimated costs of device disposables that included an assumption table, net present value (NPV) analysis, and sensitivity analysis to examine device disposable costs over 5 years with different case volumes and device mixes. To demonstrate the function of the analysis, we included four device options using the following assumptions: 100 cases in year 1, 2.5% case growth rate, 10% discount rate, and $5, 000 incremental cost (Device 4 only). Using estimated device costs of $3, 000, $12, 000, $13, 000, and $20, 000 and device mix percentages of 65%, 8%, 25%, and 2% for Device 1, 2, 3, and 4, respectively, the 5 year unadjusted and NPV of disposable device costs were $3, 691, 000 and $2, 765, 000, respectively. The sensitivity analysis incorporated six separate models with different device mix percentages. The highest and lowest estimated costs were found in Model F (75% Device 3 and 25% Device 4; NPV = $6, 64, 400) and Model B (100% Device 1; NPV = 1, 246, 000) respectively. Extracorporeal life support programs may apply this disposable cost analysis tool to reduce programmatic costs.